2015
DOI: 10.1155/2015/648128
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study of Intrahemispheric Association Fibers in the Brains of Capuchin Monkeys (Sapajussp.)

Abstract: Previous studies suggest that the complexity of fiber connections in the brain plays a key role in the evolutionary process of the primate brain and behaviors. The patterns of brain fiber systems have been studied in detail in many nonhuman primates, but not in Sapajus sp. Behavioral studies indicated that Sapajus sp. (bearded capuchins) show highly cognitive behaviors such as tool use comparable to those in other nonhuman primates. To compare the brain fiber systems in capuchins with those in other nonhuman p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Figure 4 shows these results. The tractography seeds, that is, the gray matter voxels that showed signifi- Tractography from the female-enlarged occipital and temporal cortex clusters reaches large portions of the inferotemporal cortex, likely via the inferior longitudinal fasciculus (Borges, Nishijo, Aversi-Ferreira, Ferreira, & Caixeta, 2015). Connections reach cortex surrounding the calcarine, inferior occipital, and posterior superior temporal sulci, where multiple regions in the ventral visual stream are located from V1 to TEO (Pinon et al, 1998;Rosa et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows these results. The tractography seeds, that is, the gray matter voxels that showed signifi- Tractography from the female-enlarged occipital and temporal cortex clusters reaches large portions of the inferotemporal cortex, likely via the inferior longitudinal fasciculus (Borges, Nishijo, Aversi-Ferreira, Ferreira, & Caixeta, 2015). Connections reach cortex surrounding the calcarine, inferior occipital, and posterior superior temporal sulci, where multiple regions in the ventral visual stream are located from V1 to TEO (Pinon et al, 1998;Rosa et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Some characteristics of Sapajus among primate species/genera could be explained by anatomical details [ 21 24 ]. M. fuscata displays characteristic behaviours such as stone handling [ 4 ], locomotor behaviour, gait position, and intermittent bipedalism, which could be explained by detailed anatomical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, anatomical and neuroimaging techniques have been used for investigating U-fiber regions in humans, monkeys, ferrets and mice. These pioneering studies demonstrated that humans have larger U-fiber regions than monkeys [7,8] but failed to identify U-fibers in mice [23]. These studies also showed that U-fibers are involved in various neurological and psychiatric diseases in humans [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…U-fibers are thought to mediate important higher-order cognitive functions of the nervous system [3,5]. Consistently, while U-fibers are observed in both humans and monkeys [3,6], they take up a larger proportion of the cerebrum in humans than they do in monkeys [7,8].…”
Section: Introductionmentioning
confidence: 95%